Dressed for Success: Hollywoodstjärnor och mode - Andersson, Therése (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2005)
The aim of this article was to discuss the relationship between Hollywood film and fashion from a cultural studies approach of film studies, where the Academy Awards of 2005 have served as a point of departure. This relationship was further viewed in the context of contemporary popular press, and theoretical questions of spectatorship concerning female film stars and fashion as expressions for identity were considered. The discussion therefore paid attention to the joint history of the stars system and the fashion industry, in which the stars themselves have been placed as trendsetters and as icons of style, something that has been frequently represented through the popular press. In this context film stars have the blurred status of — at the same time — being produced images and private persons. This system of representation in conjunction with spectatorship, were discussed in relation to questions of identity and self-image, body and aesthetics, as well as reception and consumption.